Cell division cycle protein 42 regulates the inflammatory response in mice bearing inflammatory bowel disease - Le-Mei Dong; Xiao-Wei Chen; Xi-Xi He; Xue-Pei Jiang; Fang Wu (Artificial Cells, Nanomedicine, and Biotechnology)
This study aimed to explore the effect of cell division cycle protein 42 (CDC42) on inflammatory response and immune response in mice bearing inflammatory bowel disease (IBD). Trinitrobenzene sulfonic acid was injected into the colon of mice to establish IBD model. The mice were divided into four groups (n = 4): control, model, Ad5, and Ad5-CDC42. After establishing IBD model, mice which were treated with AD5 empty vector and AD5-CDC42 expression vector served as the Ad5 group and Ad5-CDC42 group, respectively. The mRNA and protein levels of interleukin 10 (IL-10), interferon-γ (IFN-γ), IL-4, and tumor necrosis factor-α (TNF-α) in the colon tissues were evaluated by RT-PCR and western blot, respectively. Their levels in the serum and colon tissues were examined by ELISA assay and immunohistochemical analysis, respectively. Their changes in the mRNA and protein levels were consistent and similar changes in the colon tissues and the serum were found among various groups. The levels of IL-10, IFN-γ, IL-4, and TNF-α were lowest in the control group. Their levels in the model group and the Ad5 group were similar (p > .05) and significantly higher than those in the control group (p < .05). In comparison with the model group and the Ad5 group, their levels were significantly reduced in the Ad5-CDC42 group (p < .05). In conclusion, the levels of inflammatory cytokines were elevated in the colon tissues and serum of IBD mice, which could be reduced by the CDC42 treatment. CDC42 regulated the inflammatory response and the innate immune response in IBD mice.